EFISIENSI TENAGA KERJA PRODUKSI KAYU LAPIS MENGGUNAKAN METODE LINE BALANCING DI PT. HARJOHN TIMBER LTD - Mondina, Resta Mondina; Roslinda, Emi; Hardiansyah, Gusti (Universitas Tanjungpura, 2019)
An efficient production process can be seen from the production process planning method considering the components of production such as labor.This research aims to analyze the degree of efficiency the number of plywood production labor with method of linebalancingin PT. Harjohn Timber Ltd and analyse the level of efficiency of the production output of plywood with the method linebalancing in PT. Harjohn Timber Ltd. Research conducted from March–April 2019. This research uses the method of observation by measuring the work time the production process which is done by as much as 5 times and supported with interview techniques to some of the workforce by as much as 25 people. The analysis of the data used, namely line balancing methods such as work stations, balance delay, line efficiency, smoothness index and output production. The results showed that the efficiency of the production including labor efficient seen from the division of types of labour, balance delay, line efficiency, smoothness index and output production. Results of line efficiency of 84.62% which means the trajectory of plywood production have been efficient. The value of the balance delay amounted to 15.37% mean waiting time on the production have been minimal, while the value of smoothness index too large IE 181.80 production pathway that indicates that in this regard yet balance.Keywords : efficiency, labor, line balancing